2009
DOI: 10.1111/j.1469-0691.2008.02240.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of Anaplasma phagocytophilum infection in wild cervids and feeding Ixodes ricinus ticks from west-central Poland

Abstract: The detection of circulating galactomannan (GM) in serum samples is an important step in the diagnosis of invasive aspergillosis (IA). The assay has been mainly explored in neutropenic patients, and is now used to monitor patients at high risk for IA. However, the performance of the assay varies greatly among studies. The objective of this study was to explore the impact of the neutrophil count on the GM serum index at the time of IA diagnosis. Ninety-nine episodes of proven or probable, microbiologically docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 4 publications
(3 reference statements)
1
14
0
Order By: Relevance
“…The infection rates of 100% in red deer, 95.4% in fallow deer, and 92.9% in roe deer estimated from our study are higher than values previously reported from Slovakia: red deer 17.5–53.1% [24, 57, 102]; fallow deer 66.7% [24], and roe deer 50–77% [24, 57, 102, 103]. The infection rates determined in this study are in the upper range of those confirmed by PCR in cervids from other countries of mainland Europe, where the values in red deer ranged between 1.5–86% [89, 104114], in fallow deer between 1.5–72.5% [42, 105, 106, 108, 110, 112, 115, 116] and in roe deer between 9.6–98.9% [38, 42, 89, 105–113, 117120]. The 88.9% infection rate in mouflon is higher than the values previously reported from Slovakia [57] and other European countries, where the prevalences ranged from 4% to 74.4% [42, 106, 110, 111].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The infection rates of 100% in red deer, 95.4% in fallow deer, and 92.9% in roe deer estimated from our study are higher than values previously reported from Slovakia: red deer 17.5–53.1% [24, 57, 102]; fallow deer 66.7% [24], and roe deer 50–77% [24, 57, 102, 103]. The infection rates determined in this study are in the upper range of those confirmed by PCR in cervids from other countries of mainland Europe, where the values in red deer ranged between 1.5–86% [89, 104114], in fallow deer between 1.5–72.5% [42, 105, 106, 108, 110, 112, 115, 116] and in roe deer between 9.6–98.9% [38, 42, 89, 105–113, 117120]. The 88.9% infection rate in mouflon is higher than the values previously reported from Slovakia [57] and other European countries, where the prevalences ranged from 4% to 74.4% [42, 106, 110, 111].…”
Section: Discussionmentioning
confidence: 68%
“…In another study from Italy, a prevalence of 11% and 5.4% was detected for nymphs/adults and larvae, respectively [129]. The prevalence in adult ticks feeding on cervids in Italy (7.3%) [116] and Poland (22.7%) [108] was lower than in our study, whereas it was comparable with the 86.1% prevalence reported from a site in Germany, where the infection rate of roe deer was as high as 98.7% [38]. Anaplasma phagocytophilum was also detected in engorged H. concinna larvae and nymphs feeding on infected roe deer and fallow deer.…”
Section: Discussionmentioning
confidence: 99%
“…Only ticks removed from roe deer were significantly more often infected with this pathogen (17) than the average questing ticks analyzed in the remaining eight studies. This observation is not surprising, since deer, and possibly other ruminants, may serve as reservoir hosts for A. phagocytophilum (11). On average, 20% of the ticks are infected by spirochetes among the six studies that examined the ticks also for the presence of these pathogens, but as many as two-thirds (67.3%) of I. persulcatus ticks may be infected (1).…”
Section: Discussionmentioning
confidence: 97%
“…In Poland, roe deer ( Capreolus capreolus ) and red deer ( Cervus elaphus ) seem to be greatly involved in the wild cycle of B. venatorum, B. divergens and A. phagocytophilum (Adamska and Skotarczak 2007 , Michalik et al 2009 , Stańczak and Michalik, unpublished). We suppose that cervids play an important role in the maintenance of these microorganisms in the TCLP and in the KLP forests as they freely migrate from one forest complex to another one.…”
Section: Discussionmentioning
confidence: 99%